An X-band nanosecond gunn oscillator - Gubanov V. P. Vladimir Petrovich; Klimov A. I. Aleksey Ivanovich; Koval’chuk O. B. Oleg Borisovich; Rostov V. V. Vladislav Vladimirovich; Konev V. Yu. Vladimir Yurievich (2010, 2010)
Title screen